Strengthening Naval Diplomacy RI-US in Intelligence, Surveillance, Reconnaissance through Cooperation Afloat Readiness and Training 2024 - Yurizki Aliyah; Jonni Mahroza; Tasdik Mustika Alam; Rudy Sutanto; Sri Patmi; Lukman Yudho Prakoso (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This research discusses the joint exercise between the Indonesian Navy, the US Navy, and the US Marines (USMC), namely Cooperation Afloat Readiness and Training (CARAT) to carry out Intelligence, Surveillance, and Reconnaissance (ISR), littoral warfare, and coastal defence missions. This research uses descriptive qualitative related to Cooperation Afloat Readiness and Training (CARAT). CARAT is implemented bilaterally to enhance the maritime partnership between Indonesia and the US. For Indonesia, building a maritime partnership with the US should focus on bilateral interests as well as regional security. For the US, the CARAT programme in Indonesia can be seen as part of an effort to strengthen its influence in Southeast Asia, including facing China's dominance in the region. Based on the above background, the researcher formulates the problem, namely how to strengthen Indonesia's cooperative relationship with the United States in the face of China's dominance in the Southeast Asian region. Data collection is obtained from literature review by collecting various articles, books, journals, or other sources.   The results of this study indicate that to strengthen Indonesia's cooperative relationship with the United States in the face of China's dominance in the Southeast Asian region, is to increase cooperation in the field of security and defence, through Cooperation Afloat Readiness and Training 2024. This will help strengthen Indonesia's defence capacity and also send a signal to China that Indonesia is not easily intimidated. It is also important to continue to build relations with China in a critical but constructive manner, by promoting dialogue and diplomacy to seek points of agreement and achieve stability in the Southeast Asian region as a whole. CARAT activities are an effective strategy in enhancing security stability in the region through maritime defence cooperation. The programme benefits partner countries in building relationships of trust, enhancing defence capabilities and combating maritime threats. To increase the effectiveness of CARAT, it is recommended that partner countries continue to be committed to the programme and maintain good cooperation with the US navy and other countries in the region.